Síntese de 2-[3h-pirazol-2-il]trifluormetilpirimidinas Alquil, aril e heteroaril substituidas - Martins, Demétrius Bernardes (2004)
This work describes a general methodology for the synthesis of a novel series of 4-alkyl, 4-aryl, heteroaryl-2-[5-methyl-4-(2-hidroxyethyl)-3-oxo-1,2-dihydro-3H-pyrazol-2-yl]-6(4)-trifluoromethylpyrimidines. The precursors β-alkoxyvinyl trihalomethyl ketones of the general formula, F3C-C(O)-C(R2)=C(R)OR1, where R= H, CH3, i-Pr, Ph, 4-OCH3Ph, 2-C4H3O, 2-C4H3S, R1= CH3, C2H5 and R2 = H, CH3, R-R2= -(CH2)3-, were obtained from trifluoroacetylation reactions of enoleters and acetals derived from alkyl, cicloalkyl, methyl Ketones and 4-substituted acetophenones, propiophenones. And the precursor amidínico synthesized from 2-acetyl-butyrolactone with aminoguanidine bicarbonate in the presence of acetate of ammonium. The compounds objective of this study was obtained from the reaction of cyclocondensation reaction of 4-alkoxy-1,1,1-trifluoro-3-alken-2-ones with 1-amidino-4-(2-hydroxyethyl)-3-methyl-3-pyrazolin-5-one in the presence of anhydrous potassium carbonate. With yield of 35-80%. All the compounds 3H-pyzolil-pyrimidine were identified by 1H, 13C and 19F NMR spectra, IR, CG-MS and the purity of the compounds confirmed for it analyzes elemental.